2021
DOI: 10.5194/tc-15-4527-2021
|View full text |Cite
|
Sign up to set email alerts
|

A lead-width distribution for Antarctic sea ice: a case study for the Weddell Sea with high-resolution Sentinel-2 images

Abstract: Abstract. Using Copernicus Sentinel-2 images we derive a statistical lead-width distribution for the Weddell Sea. While previous work focused on the Arctic, this is the first lead-width distribution for Antarctic sea ice. Previous studies suggest that the lead-width distribution follows a power law with a positive exponent; however their results for the power-law exponents are not all in agreement with each other. To detect leads we create a sea-ice surface-type classification based on 20 carefully selected cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Overall, our algorithm exhibited the capability to accurately identify 87.16% of the lead structures. A previous study showed that band 4 (665 nm) of Sentinel-2 is the best choice for SIL identification [22]; thus, the reflectance of band 4 was chosen for comparison with the identification results for evaluation in this paper. The comparison of SILs detected from Sentinel-2 images and MODIS images is depicted in Figure 3, which is arranged in the order, Sentinel-2 original band 4 image, Sentinel-2 leads map, and MODIS leads map.…”
Section: Precision Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our algorithm exhibited the capability to accurately identify 87.16% of the lead structures. A previous study showed that band 4 (665 nm) of Sentinel-2 is the best choice for SIL identification [22]; thus, the reflectance of band 4 was chosen for comparison with the identification results for evaluation in this paper. The comparison of SILs detected from Sentinel-2 images and MODIS images is depicted in Figure 3, which is arranged in the order, Sentinel-2 original band 4 image, Sentinel-2 leads map, and MODIS leads map.…”
Section: Precision Evaluationmentioning
confidence: 99%
“…In contrast, research on Antarctica SIL primarily focused on the identification algorithm [21,22], and there is a need for more comprehensive research to explore the distribution characteristics of SILs and their correlation with meteorological and hydrological factors. A notable oceanographic feature in the Southern Ocean is the Weddell Gyre (WG).…”
Section: Introductionmentioning
confidence: 99%
“…Satellites have monitored the spatial distribution and temporal evolution of Arctic lead fraction since the 1990s (Key et al, 1993;Lindsay and Rothrock, 1995;Miles and Barry, 1998). Lead detection based on thermal infrared (TIR, Willmes and Heinemann, 2016;Hoffman et al, 2022;Wang et al, 2022;Qiu et al, 2023) and visible images (e.g., Lewis and Hutchings, 2019;Muchow et al, 2021) was complemented by classification of Synthetic Aperture Radar (SAR) backscatter (e.g., Murashkin et al, 2018), radar altimeters (e.g., CryoSat-2 Hendricks et al, 2021a), laser altimeters (e.g, ICESat-2 Duncan and Farrell, 2022), and passive microwave (PMW) data (e.g., Röhrs et al, 2012). The transient nature of leads and their narrow appearance sets limits to the detection of leads from satellites.…”
mentioning
confidence: 99%